Mechanisms Underlying the Vasorelaxant Effect Induced by Proanthocyanidin-Rich Fraction From Croton celtidifolius in Rat Small Resistance Arteries - Silvia DalBó; Eduardo Gasnhar Moreira; Fernanda Costa Brandão; Heros Horst; Moacir Geraldo Pizzolatti; Gustavo Amadeu Micke; Rosa Maria Ribeiro- (Elsevier, 2008)
Proanthocyanidins are condensed tannins present in fruits, vegetables, and flowers, consumed in the human diet. These compounds are believed to decrease coronary heart disease. The present study was designed to investigate the relaxing effects of a proanthocyanidin-rich fraction (PRF) obtained from Croton celtidifolius BAILL (Euphorbiaceae) barks in rat mesenteric arterial bed (MAB) and isolated mesenteric artery (MA). In the MAB pre-contracted with phenylephrine (Phe), PRF (0.1 -100 μ g) induced a concentration-dependent relaxation of 73% (compared to the control). This effect was significantly reduced by the nitric oxide (NO) synthase inhibitor Nω-nitro-L-arginine (L-NOARG) or high K+solution and completely abolished in vessels perfused with KCl plus L-NOARG. However, the vasorelaxant effect was not altered by indomethacin, atropine, yohimbine, pyrilamine, or K+-channel blockers: BaCl2, glibenclamide, ouabain, and 4-aminopyridine. In isolated MA pre-contracted with Phe, PRF also induced a concentration-dependent relaxation (0.1 -30 μ g/mL), which was in turn inhibited by endothelial removal, guanylyl cyclase inhibitor 1H [1,2,3]oxadiazolo[4,3-alpha]quinoxalin, charybdotoxin (ChTx), and ChTx plus apamin. Moreover, the relaxant effect was not altered by HOE140 and apamin given alone. The present study demonstrates that the vasorelaxing effect of PRF is dependent upon the NO-cGMP pathway in combination with hyperpolarization due to activation of Ca2+-dependent K+channels. Keywords:: Croton celtidifolius, proanthocyanidin, vasorelaxation, nitric oxide (NO), K+channel